Искусительница, или Капкан на ялтинского жениха - Шилова Юлия (Криминальная мелодрама, 2009)
Экземпляры: ХР (20181204) / Инвентарный номер: 44813 / Цена: 20 / Сис.шифр: Р 2 / Авт.знак: Ш 59 / ГРНТИ: 17.82.30 / ББК: 84(2Рос=Рус)6